2010
DOI: 10.1038/cr.2010.84
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of active and repressive histone methylations by a dual-specificity histone demethylase ceKDM7A from Caenorhabditis elegans

Abstract: H3K9me2 and H3K27me2 are important epigenetic marks associated with transcription repression, whileH3K4me3 is associated with transcription activation. It has been shown that active and repressive histone methylations distribute in a mutually exclusive manner, but the underlying mechanism was poorly understood. Here we identified ceKDM7A, a PHD (plant homeodomain)-and JmjC domain-containing protein, as a histone demethylase specific for H3K9me2 and H3K27me2. We further demonstrated that the PHD domain of ceKDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Thus, substrate binding is not required to maintain its structure. Lin et al addressed the role of the PHD of ceKIAA1718 in vivo [10]. The PHD deletion mutant expressed in Tn5 cells using a baculovirus system does not show demethylase activity against H3K9me2 and H3K27me2 [10], which is not consistent with the crystal structure data.…”
mentioning
confidence: 72%
“…Thus, substrate binding is not required to maintain its structure. Lin et al addressed the role of the PHD of ceKIAA1718 in vivo [10]. The PHD deletion mutant expressed in Tn5 cells using a baculovirus system does not show demethylase activity against H3K9me2 and H3K27me2 [10], which is not consistent with the crystal structure data.…”
mentioning
confidence: 72%
“…Cocrystal structures of ceKDM7A with H3K4me3-containing peptides bound to the PHD finger and H3K9me2 or H3K27me2 peptides bound to the JmjC domain indicate that binding of the peptides does not cause significant conformational changes (Supplementary information, Figure S2A-S2C), suggesting that each domain can perform their biochemical functions independently. Consistently, a fragment containing only the PHD finger can bind to H3K4me3-containing peptide, and disrupting the interaction between the PHD finger and H3K4me3 did not affect the demethylase activity of the JmjC domain in vitro (Lin et al, accompanying paper in this issue [33]). However, the PHD finger binding to H3K4me3 is required for demethylation by the JmjC domain in vivo.…”
Section: Cross-regulation Of Histone Demethylasesmentioning
confidence: 79%
“…We also found that its C. elegans ortholog ceKDM7A, a PHDand JmjC domain-containing protein, is a histone demethylase specific for H3K9me2 and H3K27me2, and the PHD finger binding to H3K4me3 guides the demethylation activity in vivo (Lin et al, accompanying paper in this issue [33]). However, the molecular mechanisms for both the enzymatic activity and the function of the PHD finger remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations